Effect of root planing on surface topography: an in‐vivo randomized experimental trial. (13th May 2014) - Rosales‐Leal, J. I.; Flores, A. B.; Contreras, T.; Bravo, M.; Cabrerizo‐Vílchez, M. A.; Mesa, F.
Abstract : Background and Objective: The root surface topography exerts a major influence on clinical attachment and bacterial recolonization after root planing. In‐vitro topographic studies have yielded variable results, and clinical studies are necessary to compare root surface topography after planing with current ultrasonic devices and with traditional manual instrumentation. The aim of this study was to compare the topography of untreated single‐rooted teeth planed in vivo with a curette, a piezoelectric ultrasonic (PU) scraper or a vertically oscillating ultrasonic (VOU) scraper. Material and Methods: In a randomized experimental trial of 19 patients, 44 single‐rooted teeth were randomly assigned to one of four groups for: no treatment; manual root planing with a curette; root planing with a PU scraper; or root planing with a VOU scraper. Post‐treatment, the teeth were extracted and their topography was analyzed in 124 observations with white‐light confocal microscopy, measuring the roughness parameters arithmetic average height, root‐mean‐square roughness, maximum height of peaks, maximum depth of valleys, absolute height, skewness and kurtosis. Results: The roughness values arithmetic average height and root‐mean‐square roughness were similar after each treatment and lower than after no treatment (  p  < 0.05). Absolute height was lower in the VOU group than in the untreated (  p  = 0.0026) and PU ( p  = 0.045) groups. Surface morphology was similar after the three treatments and was less irregular than in the untreated group. Values for the remaining roughness parameters were similar among all treatment groups (  p  > 0.05). Conclusion: Both ultrasonic devices reduce the roughness, producing a similar topography to that observed after manual instrumentation with a curette, to which they appear to represent a valid alternative.